A Comparative Study of American and Moroccan University Students’ Perception of Academic Writing - Nadia Hellalet (Journal of English Language Teaching and Linguistics, 2021)
The study attempts to investigate native speakers’ and non-native speakers’ perceptions of writing quality. Thirty-seven American freshmen students and forty Moroccan semester two students participated in the study. An email interview was used to explore the similarities and differences between the students’ views on what makes good academic writing. Both American and Moroccan Students were asked about the different features of academic writing that can contribute to its quality. The research findings revealed that most of the American students focused on the content of the paper. They stated that it should be exciting and engaging. It should also have depth and grab the reader’s attention. Many of them mentioned the reader in their responses. They noted that writing should be easy to read and respond to the readers’ expectations. On the other hand, Moroccan students focused on the form of paper, including language and conventions. They put correct grammar and vocabulary on top of their list. Good writing style, good sentence structure, spelling, punctuation, simple language, and coordination are necessary elements. The study has pedagogical implications that can benefit writing teachers.